Edukasi Pentingnya Menjaga Kesehatan Mental Pada Anak Remaja Di SMA Negeri 3 Binjai - Hrp, Fitri Aidani Ulfa; Mastari, Ekawaty Suryani; Wahyuni, Ningrum; Tarigan, Emilia Putri; Nuha, Farhah Kamilatun (Marsipature Hutanabe: Jurnal Pengabdian Kepada Masyarakat, 2024)
Mental health problems have become unresolved health problems in society, both at the global and national levels. Especially during the COVID-19 pandemic, mental health problems will be more difficult to solve. The increasingly concerning condition of people's mental health will affect national productivity. This could hinder Indonesia from transitioning into a developed country by 2045. Mental health services are crucial and require the same attention as physical health. According to the Indonesia-National Adolescent Mental Health Survey 2022, 15.5 million (34.9 percent) adolescents experience mental problems and 2.45 million (5.5 percent) adolescents experience mental disorders. Of that number, only 2.6 percent accessed counseling services, both emotional and behavioral. The government has been thinking about mental health, but it has not been a priority. Access to mental health services is expensive and not inclusive. Meanwhile, attention to mental and physical health has not been equal in national health insurance. In Indonesia, we know many cases of adolescents aged 15-17 who experience excessive anxiety resulting in depression and suicide.